Introdução à Teoria dos Grafos - Soares de Melo, Gildson (2014)
This paper presents an introductory study of graph theory, considering its relevance to the teaching of mathematics. Initially presents a brief history on Graph Theory. Then the rst chapter consists of some de nitions on graphs and examples, the second chapter deals with the paths, walks and cycles in a graph, highlighting the Eulerian tours and Hamiltonian cycles, also boarded a special type of graphs, trees . In Chapter 3 we address the planarity in graphs, thus presenting Euler's Formula. Finally in Chapter 4 we present some problems involving graphs.